Effect of Electrode Selection on Impact Toughness in Weld Metal of Rail Steel Grade 900A - Poolsiri, Nutchanon; Petchsang, Salita; Tehyo, Muhamad; Sani, Suhaidee; Muangjunburee, Prapas (Princess of Naradhiwas University Journal, 2021)
The objective of this research was to investigate electrode types on impact toughness of rail steel grade 900A repaired by the Shielded Metal Arc Welding (SMAW) process. Three different types of electrodes, which provide similar hardness of the weld metal compared to that of the rail steel base metal, were examined. The results found that the microstructure of the weld metal mostly consisted of bainite. The bainite structure in the weld metal depended on the chemical composition of each weld metal. Moreover, the impact toughness of each sample was different due to various carbon contents in the weld metal. In this research, the weld metal contained bainite and ferrite structures showed the highest impact toughness.